Trm1p, a Zn(II)(2)Cys(6)-Type Transcription Factor, Is a Master Regulator of Methanol-Specific Gene Activation in the Methylotrophic Yeast Candida boidinii - Sasano, Yu (American Society for Microbiology (ASM), 2008)
The methylotrophic yeasts are commonly used as hosts for heterologous gene expression. In this study, we describe a novel gene, TRM1, in Candida boidinii, responsible for the transcriptional activation of several methanol-inducible promoters. The encoded protein, Trm1p, is a Zn(II)(2)Cys(6)-type zinc cluster protein. Deletion of TRM1 completely inhibits growth on methanol but causes no growth defect on glucose or other nonfermentative carbon sources, glycerol, ethanol, or oleate. Trm1p is responsible for transcriptional activation of five methanol-inducible promoters tested, but not for peroxisome assembly or peroxisomal protein transport. Expression of the TRM1 gene was constitutive, and Trm1p localizes to the nuclei regardless of the carbon source. Two cis-acting methanol response elements (MREs), MRE1 and MRE2 are present in the promoter of the dihydroxyacetone synthase gene. Trm1p is shown to be required for MRE1-dependent methanol-inducible gene expression. Chromatin immunoprecipitation assays reveal that Trm1p binds to five methanol-inducible promoters upon methanol induction but does not bind in glucose-grown cells. Thus, the TRM1 gene encodes a master transcriptional regulator responsible for methanol-specific gene activation in the methylotrophic yeasts.